The Legal Framework for Interfaith Marriage in Indonesia: Examining Legal Discrepancies and Court Decisions - Bisri, Hasan (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2023)
Interfaith marriage has been regulated in Law No. 1/1974 on Marriage and various other legal regulations. However, there are several different or even conflicting court decisions regarding cases of interfaith marriage. This continues even after the issuance of Supreme Court Circular Letter No. 2 of 2023 (known as SEMA No. 2 of 2023), which has become a reference for judges in deciding cases of interfaith marriage. This article examines the legal framework of interreligious marriage in Indonesia by focusing on the various judges' interpretations of legal regulations on interfaith marriage. Using normative legal analysis with empirical data and utilizing the theory of legal pluralism developed by Brian Z. Tamanaha, this article concludes that different perspectives on the protection of citizens' human rights in marriage and the role of religion as a state philosophy have significantly contributed to variations in judges' interpretations of several legal regulations on interfaith marriage. The differences in judges' interpretations have ultimately resulted in differences in legal decisions. This has become a recurring dynamic in judges' understanding of legal regulations on interfaith marriage.   Perkawinan beda agama telah diatur dalam UU No. 1 Tahun 1974 tentang Perkawinan dan juga berbagai peraturan hukum lainnya. Namun demikian, terdapat sejumlah putusan pengadilan yang berbeda atau bahkan saling bertentangan menyangkut perkara perkawinan beda agama. Hal ini bahkan terus berlanjut pasca keluarnya Surat Edaran Mahkamah Agung No. 2 Tahun 2023 (dikenal dengan SEMA No. 2 Tahun 2023) yang menjadi acuan para hakim dalam memutus perkara perkawinan beda agama. Artikel ini mengkaji kerangka hukum perkawinan beda agama di Indonesia dengan berfokus pada ragam penafsiran hakim atas peraturan hukum tentang perkawinan beda agama. Menggunakan analisis hukum normatif dengan data empiris dan dengan memanfaatkan teori pluralisme hukum yang dikembangkan oleh Brian Z. Tamanaha, artikel ini menyimpulkan bahwa perbedaan perspektif tentang perlindungan hak asasi warga negara dalam perkawinan dan peran agama sebagai falsafah negara, secara signifikan telah berkontribusi pada variasi penafsiran hakim atas sejumlah peraturan hukum tentang perkawinan beda agama. Perbedaan interpretasi hakim itulah yang pada akhirnya berdampak pada perbedaan putusan hukum. Hal ini telah menjadi dinamika yang berulang dalam interpretasi hakim atas peraturan hukum tentang perkawinan beda agama.